(untitled) (Bangladesh Pharmaceutical Journal, 2021)
Bangladesh is a land of thousands of plants which might provide a scope to obtain therapeutically important natural drugs. Systematic screening of plants is very vital to fulfill this goal. Quisqualis indica (L.) is a vine and it belongs to the Combretaceae family. It grows all over the Bangladesh. It has some local uses to treat headache, skin disease, diarrhea, fever, cough, etc. In order to assess its biological potential, the leaves of the plant were collected and subjected to methanol extraction followed by fractionating into petroleum ether, carbon tetrachloride, chloroform and aqueous soluble materials. Primary free radical scavenging power of the extractives was evaluated using the radicals generated by DPPH and H2O2. Methanol crude extract as well as aqueous and chloroform fractions showed noticeable radical scavenging potential. Besides, these extracts had higher level of phenolics. The membrane stabilizing potential of the extractives was estimated based on the prevention of hemolysis of RBC prompted by hypotonic solution as well as heat. The aqueous fraction showed the highest level of membrane stabilizing potential indicating its primary anti-inflammatory ability. The extractives were also subjected to thrombolytic study. Mild thrombolytic ability was displayed by them compared to the standard. Further studies are required to explore bioactive compounds. Bangladesh Pharmaceutical Journal 24(2): 99-104, 2021